Genetic relationship among papaya (Carica papaya) and wild papaya (Vasconcellea species) using RAPD and ISSR markers - KANUPRIYA, KANUPRIYA; SHOBHANA, M; VASUGI, C; ASWATH, C; RADHIKA, V; REDDY, LAXMAN; DINESH, M R (The Indian Journal of Agricultural Sciences, 2012)
Two different molecular methods namely, Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeats (ISSR) were used to measure genetic diversity among thirteen commercially important cultivars of papaya and two species of useful wild papaya. Eleven ISSR and 16 RAPD primers were screened to amplify a total of 75 and 118 bands respectively. Of these, approximately 35% and 37.2% of the bands were polymorphic in each. Genetic similarity was computed and results displayed graphically as dendrogram generated by UPGMA cluster analysis showing the relationships among wild and cultivated papaya cultivars. Both methods revealed different groupings of the eleven cultivars of papaya. On the basis of correlation of data with morphological grouping based on fruit pulp colour and plant height, ISSR was judged to be best method for analyzing all papaya germplasm.